Pengujian Panel Fotovoltaik Dengan Variasi Sudut Kemiringan - Simanullang, Dohardo P.H.; Zakri, Azriyenni Azhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Photovoltaic system serves to convert solar energy into electrical energy or DC voltage. This study aims to test and observe the absorption of solar intensity by photovoltaic panels atvarious angles of the slope. The photovoltaic panel absorbs the maximum solar intensity if the photovoltaic panel is perpendicular to the coming sunshine. The method used to determine theangle of the photovoltaic panel is by observing the voltage and current values of the photovoltaic panel output. The Testing has been conducted with several variations of slope angles, namely; at an angle of 30 °, 40 °, and 50 °. From the results of tests and observations, it has been found that the absorption of solar intensity with maximum power (66 watts) occurs at the slope angle of 40 °.Keywords: slope angle, solar energy, solar absorption, photovoltaic